Repeatability of the Six-Minute Walk Test and Relation to Physical Function in Survivors of a Critical Illness - Alison, J.; Kenny, P.; King, M.; McKinley, S.; Aitken, L.; Leslie, Gavin; Elliott, D. (American Physical Therapy Association, 2012)
Background: The Six-Minute Walk Test (6MWT) is widely used as an outcome measure in exercise rehabilitation. However, the repeatability of the 6MWT performed at home in survivors of a critical illness has not been evaluated. Objective: The purpose of this study was to evaluate, in survivors of a critical illness: (1) the repeatability of the 6MWT performed at home, (2) the effect on estimates of change in functional exercise capacity if only one 6MWT was performed at follow-up assessments, and (3) the relationship between the physical functioning (PF) score of the 36-Item Short-Form Health Survey questionnaire (SF-36) and the 6MWT. Design: Repeated measures of the 6MWT and SF-36 were obtained. Methods: Eligible participants had an intensive care unit (ICU) length of stay of ≥48 hours and were mechanically ventilated for ≥24 hours. Two 6MWTs and the SF-36 were conducted in participants' homes at weeks 1, 8, and 26 after hospital discharge. Results: One hundred seventy-three participants completed the study. The participants had a mean age of 57 years (SD=16), a mean Acute Physiology and Chronic Health Evaluation II (APACHE II) score on admission of 19 (SD=10), a mean ICU length of stay of 9 days (SD=8), and a mean mechanical ventilation time of 140 hours (SD=137). Of the 173 participants, 110 performed two 6MWTs at weeks 1, 8, and 26. There were significant mean increases in 6-minute walk distance in the second test of 15 m (P<.0001) at week 1, 13 m (P<.0001) at week 8, and 9 m (P=.04) at week 26. If only one 6MWT was performed at weeks 8 and 26, the estimate of change in 6-minute walk distance from week 1 was 19 m less (P<.001) at both weeks 8 and 26. There was a moderate to strong correlation between SF-36 PF score and 6-minute walk distance at each assessment (week 1: r=.62, P<.001; week 8: r=.55, P<.001; and week 26: r=.47, P<.001).Limitations: Some study participants were unable to perform a second 6MWT, and these participants may have differed in important aspects of function compared with those individuals who completed two 6MWTs. Conclusions: In survivors of a critical illness, the 6MWT in the home environment should be performed twice at each assessment to give an accurate reflection of change in exercise capacity over time. The SF-36 PF score was a strong indicator of 6-minute walk distance in early recovery from a critical illness.